Secure Attachment in Early Childhood Centers: Theoretical, Methodological, and Practical Guidelines for Respectful Care of Children Under Three (Innovaciones Educativas, 2025)
The enrollment of children under the age of three in educational institutions has been increasing, presentinga series of challenges for families and early childhood educators. This manuscript systematizes the work carriedout over the past decade at the Centro Infantil Laboratorio Ermelinda Mora (CILEM) to establish a respectful transitionprocess for young children and to foster secure attachment within the educational environment. The analysis of the dissonances between theoretical frameworks and classroom practices began with a collaborative reading of coreprinciples of early childhood development. Subsequently, classroom routines were recorded on video and analyzed collectively with educators to reflect on the alignment between guiding principles and actual practices. The manuscripthighlights key theoretical foundations essential for working with children under the age of three and outlinesthe process of professional development and reflective practice undertaken by the staff. It also presents pedagogical and relational strategies that have proven effective in transforming institutional practices. The process of reflectionand action enabled a deeper examination of everyday routines—often carried out automatically—uncoveringunderlying developmental goals and worldviews. The main outcome of this process was the creation of a sharedinstitutional language, developed through interdisciplinary dialogue, and a more sensitive response to the needs of both families and young children, resulting in a positive impact on learning and development.
Keywords: developmental psychology; early childhood development; emotional development; educational strategies; early childhood program; preschool educator